Effect of salinity stress and its potential application in enhancing phytochemical content of medicinal plants - Yan, Lam Chi; Naharudin, Nazatul Shima; Tajidin, Nor Elliza; Kemat, Nurashikin (CAB International, 2023)
Medicinal plants are considered as high-value crops, particularly in the medicinal and pharmaceutical fields. The phytochemical constituents found in medicinal plants that possess therapeutic effects have henceforth driven continuous demand for the manufacturing of healthcare products that include these compounds as the main ingredients. Various agronomic practices in the cultivation of medicinal plants aim to increase the yield and phytochemical content. A thorough review on the implication of salinity stress on the growth and yield of medicinal plants were provided. The increased level of phytochemicals as a common physiological response to salinity stress was reported in various species of medicinal plants. The potential application of a tolerable level of salinity in the cultivation of medicinal plants as a strategy to increase the production of phytochemical compounds is also highlighted.